Pengaruh Pengendalian Internal Dan Kesesuaian Kompensasi Organisasi Terhadap Kecenderungan Kecurangan Akuntansi - Putri Marliana Nuril Azmi; Dirvi Surya Abbas; Kimsen Kimsen (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this study was to determine the effect of internal control and compensation suitability on the tendency of accounting fraud at PT Bank Central Asia Tbk KCU Alam Sutera. This research method uses qualitative methods by distributing research questionnaires. The population of this study includes all employees who work at the BCA KCU Alam Sutera bank. The sampling technique used is simple random sampling technique. In this study the authors use SPSS 26 in data processing. The results showed that internal control, compensation suitability and organizational ethical culture had an effect on the tendency of accounting fraud. Internal control, compensation suitability and organizational ethical culture together affect the tendency of accounting fraud.